Association between Stroke History and Clinical Events in Atrial Fibrillation Patients after Valve Replacement - Xinsheng Yan; Shuwen Lian; Dong Wang; Bao Yan; Litao Zhang; Zhenlu Zhang (Reviews in Cardiovascular Medicine)
Background: The association between stroke history and clinical events after valve replacement in patients with atrial fibrillation (AF) combined with valvular heart disease (VHD) is unclear. Thus, we sought to investigate the relationship between stroke history and clinical events in patients with AF after valve replacement. Methods: This retrospective cohort study enrolled 746 patients with AF who underwent valve replacement between January 2018 and December 2019 at the Wuhan Asia Heart Hospital. Patient information was collected from the hospital’s electronic medical record system. Patients were categorized based on their stroke history and followed through outpatient visits or by telephone until the occurrence of an endpoint event; the maximum follow-up period was 24 months. Endpoint events included thrombotic events, bleeding, and all-cause mortality. The frequency of thrombotic, hemorrhagic, and fatal events during the follow-up period was compared between the two groups. Independent risk factors for endpoint events were analyzed using multifactorial Cox regression. Results: The analysis included 746 patients. Over a 24-month follow-up period, there were more total adverse events (hazard ratio (HR) = 2.08, 95% confidence interval (CI) 1.06–4.08, p = 0.018), thrombotic events (HR = 10.28, 95% CI 2.85–37.11, p < 0.001), and increased all-cause mortality (HR = 5.74, 95% CI 1.84–17.93, p < 0.001) in the stroke history group than in the non-stroke history group. Fewer bleeding events were observed in the group with a history of stroke (HR = 0.87, 95% CI 0.37–2.04, p = 0.757). A multifactorial Cox regression analysis revealed that a personal history of stroke was an independent risk factor for total adverse events, thrombotic events, and all-cause mortality. Conclusions: Previous stroke history is significantly associated with adverse events in AF patients following valve replacement.